Potensi Simpanan Karbon pada Beberapa Tipologi Hutan Rawa Gambut di Kalimantan Tengah - Muhammad Abdul Qirom; Tri Wira Yuwati; Purwanto Budi Santosa; Wawan Halwany; Dony Rachmanadi (Jurnal Ilmu Kehutanan, 2018)
Akurasi pendugaan simpanan karbon hutan rawa gambut dapat ditingkatkan melalui pengukuran masing-masing gudang/sumber karbon dan berbagai macam tipologi hutannya. Pengukuran tersebut berkaitan dengan besarnya kandungan dan fraksi simpanan karbon pada masing-masing gudang karbon. Penelitian ini bertujuan untuk mendapatkan kandungan dan potensi simpanan karbon pada masing-masing gudang karbon di tipologi gambut. Pengukuran simpanan karbon dilakukan pada lima gudang karbon yakni vegetasi (tingkat permudaan pohon), serasah, tumbuhan bawah, nekromasa dan tanah. Hasil penelitian menunjukkan kandungan karbon adalah 50% dari berat kering biomassa. Kandungan karbon tidak dipengaruhi oleh gudang karbon dan tipologi gambut. Pada tanah gambut, kedalaman gambut mempengaruhi besarnya kandungan karbon sehingga besarnya faktor konversi harus memperhatikan kedalaman masing-masing tipologi gambut. Potensi simpanan karbon terbesar pada tipologi hutan sekunder dengan kedalaman gambut antara 3-3,5 m sebesar 3.722,08 Mg/ha sedangkan potensi simpanan karbon terendah pada tipologi semak belukar dengan kedalaman gambut 3-3,5 m sebesar 2243,49 Mg/ha. Pada hutan gambut, gudang karbon tanah menyumbang >95% dari simpanan karbon total. Gudang karbon nekromasa memberikan sumbangan simpanan karbon terkecil. Fraksi simpanan karbon pada masing-masing gudang karbon berturut-turut adalah tanah> vegetasi> serasah> tumbuhan bawah> nekromasa.Carbon Stocks Potential of Peatland Forests Typologies in Central KalimantanAbstractAccuracy of carbon stocks estimation can be enhanced by measuring each carbon pools in various forest peatland typologies. The carbon stocks measurement is associated with the amount of contents and fractions of carbon stocks. The research objectives were to obtain the information of carbon contents and carbon stocks potentials in each carbon pool in the peat typologies. Carbon stocks measurement was conducted in five carbon pools which were: vegetation (tree stages), litter, understory, necromass, and soil. The results showed that the carbon contents reached more than 50% of its dry weight. The carbon contents were not affected by the carbon pools and peat typologies. In the soil carbon pools, peat depth affected the amount of carbon content so that the magnitude of the conversion factor should concentrate to the depth of each peat typology. The greatest potential of carbon stocks was found in the secondary forest (3,733.08 Mg/ha) with the peat depths between 3-3.5 m, while the lowest potential of carbon stocks found in the bush typology (2243.49 Mg/ha) with the peat depths between 3-3.5 m. In the peat typology, soil carbon stocks contributed more than 95% of total carbon stocks whereas necromass carbon stocks contributed the smallest amount of carbon. The fractions of carbon stocks in each carbon pools were soil> vegetation> litter> understorey> necromass, respectively.